Students’ Attitudes toward Hybrid Teaching Model - Nanda Dwi Putri (Teaching English and Language Learning English Journal, 2021)
Hybrid teaching is teaching that uses an online multimedia learning system but does not disappear face-to-face sessions, the students hybrid teaching models attitudes at class. This research has been conducted using a qualitative descriptive method. According to Meleon (2011) qualitative research is a research procedure that intends to understand the phenomenon of what is experienced but research subjects holistically (intact). The aim of the research to find out Students hybrid teaching mode attitudes at class. The researcher describes the results of this study. The researcher found several forms of students'' attitudes towards hybrid teaching. Researchers gave questionnaires to students who had done online learning data collection was carried out on August 7-11, 2021). The questionnaire is based on Meleon (2011) regarding: students' attitudes towards English class face-to-face and blended learning instructions. Based on the results of research and discussion, it shows that the percentage of students' attitudes towards hybrid teaching is at a moderate level. Where the sufficient level is 76%-100% Sufficient or Good which is shown in the percentage table. Students' attitudes towards hybrid teaching are at a high level.Keywords: Students’ Attitudes, Hybrid Teaching Model